Identification of the DDAH2 Protein in Pig Reproductive Tract Mucus: A Putative Oestrus Detection Marker. Issue 1 (27th June 2012) - Lee, WY; Chai, SY; Lee, KH; Park, HJ; Kim, JH; Kim, B; Kim, NH; Jeon, HS; Kim, IC; Choi, HS; Song, H
Contents: Precisely detecting oestrus is important for artificial insemination. The aims of this study were to identify oestrus‐specific sow mucus proteins to determine the optimal time for artificial insemination. The proestrous‐ and oestrous‐stage mucus proteins were purified and analysed with proteomic tools such as two‐dimensional gel electrophoresis and matrix‐assisted laser desorption/ionization–time‐of‐flight analyses. Among the differentially expressed proteins, the dimethylarginine dimethylaminohydrolase 2 (DDAH2) protein showed a 3.6‐fold increase during the proestrous stage compared to that during the oestrous stage. A western immunoblot study revealed that two of three sow mucus samples clearly showed negative anti‐DDAH2 antibody activity during the oestrous stage. This study demonstrated that the pig DDAH2 mucus protein exists during the proestrous stage, but not during the oestrous stage, suggesting that mucus DDAH2 could be useful as an oestrus detection marker.